2019
DOI: 10.1002/tafs.10135
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Ecology of Sheepshead and Stone Crabs at Oil and Gas Platforms in the Northern Gulf of Mexico's Hypoxic Zone

Abstract: Oil and gas platforms (platforms) may provide important habitat for reef‐associated organisms in the Gulf of Mexico's hypoxic zone. While summer hypoxia typically affects the bottom 3.0 m of the water column, platforms span from the bottom to above the surface and provide hard substrate in oxygenated waters overlaying hypoxia. However, little is known about the effects of hypoxia on organisms living at these platforms. We compared diets of Sheepshead Archosargus probatocephalus and Gulf stone crabs Menippe adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Previous studies in shallow coastal environments revealed that assemblages on artificial substrates were not identical to that of adjacent natural substrates as they offer atypical surfaces in terms of orientation, depth range and surface [72,73]. Foraging also plays an important role in shaping the assemblages on artificial structures [74]. The influence of these factors in determining the mesoscale patterns of macrofoulant assemblages on artificial structures have to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in shallow coastal environments revealed that assemblages on artificial substrates were not identical to that of adjacent natural substrates as they offer atypical surfaces in terms of orientation, depth range and surface [72,73]. Foraging also plays an important role in shaping the assemblages on artificial structures [74]. The influence of these factors in determining the mesoscale patterns of macrofoulant assemblages on artificial structures have to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It was not listed by Gallaway and Lewbel (1982) as even being present on Gulf platforms, nor was it listed as being seen at coastal platforms in the northern Gulf by Wilson (1997, 2003) or by Stunz et al (2016) for platforms offshore south Texas. In contrast, Reeves (2015), Munnelly (2016) and Reeves et al (2019) observed Atlantic Bumper were abundant at coastal platforms offshore Louisiana by the mid 2000's.…”
Section: Species Assemblage Structurementioning
confidence: 96%
“…The postlarvae of many decapod species select complex habitats for metamorphosis (Wolcott & DeVries 1994, Stevens & Kittaka 1998, Pardo et al 2007, Webley et al 2009; and high turbidity can deter aquatic predators that rely on visual prey recognition (Reustle & Smee 2020), as well as those that do not (Ortega et al 2020). The cannibalistic nature of stone crabs of all sizes (Yang & Krantz 1976, Krimsky 2008) and susceptibility of YOY stone crabs to predation by other animals (Frick & Mason 1998, Schmid 1998, Scharf & Schlicht 2000, Shervette et al 2004, Reeves et al 2019 suggests that, as in other species (Kurihara & Okamoto 1987, Fernandez 1999, Luppi et al 2001, Pirtle & Stoner 2010, refuge from predation is important in habitat selection by stone crab megalopae and PS-juveniles. Complex shelters with small openings have been shown to reduce interspecific and intraspecific competition and predation on YOY Menippe adina and enhance the density and survival of all sizes of juveniles (Gibbs 1994).…”
Section: Physical Conditionsmentioning
confidence: 99%